Correction of gradient nonlinearity artifacts in prospective motion correction for 7T MRI - Uten Yarach (2018)
© 2014 Wiley Periodicals, Inc. Purpose To demonstrate the effect of gradient nonlinearity and develop a method for correction of gradient nonlinearity artifacts in prospective motion correction (Mo-Co). Methods Nonlinear gradients can induce geometric dist ortions in magnetic resonance imaging, leading to pixel shifts with errors of up to several millimeters, thereby interfering with precise localization of anatomical structures. Prospective Mo-Co has been extended by conventional gradient warp correction applied to individual phase encoding steps/groups during the reconstruction. The gradient-related displacements are approximated using spherical harmonic functions. In addition, the combination of this method with a retrospective correction of the changes in the coil sensitivity profiles relative to the object (augmented sensitivity encoding (SENSE) reconstruction) was evaluated in simulation and experimental data. Results Prospective Mo-Co under gradient fields and coils sensitivity inconsistencies results in residual blurring, spatial distortion, and coil sensitivity mismatch artifacts. These errors can be considerably mitigated by the proposed method. High image quality with very little remaining artifacts was achieved after a few iterations. The relative image errors decreased from 25.7% to below 17.3% after 10 iterations. Conclusion The combined correction of gradient nonlinearity and sensitivity map variation leads to a pronounced reduction of residual motion artifacts in prospectively motion-corrected data.